Strategi Pengembangan Usahatani Lada Perdu (Piper Nigrum L.) Desa Epeea Kecamatan Abuki Kabupaten Konawe - Milawati Saranani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This study aims to analyze the development strategy of pepper farming in Epeea Village, Abuki District, Konawe Regency. The method used to determine the number of samples is to use (Saturated Sample/Census). Saturated sample is a sampling method where all members of the population are taken 12 as sample members. The results of the IFAS (internal analysis summary) matrix calculation show that the total value of the internal factors is 3.0. The results of the EFAS (External Analysis Summary) matrix calculation show that the total value of the external factors is 2.8. Based on the results of the SWOT analysis above, the strategy that can be applied in Pepper Farming is an Aggressive strategy formed in quadrant I. Where Strength + Opportunity (1.34)> Weakness + Threats (0.65), then the Strategic factors of strength and opportunity support the achievement of a way out of the existing problems to achieve the desired goals. So that Pepper Farming in Epeea Village, Abuki District, Konawe Regency can survive and grow even bigger.